2021
DOI: 10.1016/j.nedt.2021.105105
|View full text |Cite
|
Sign up to set email alerts
|

COVID 19-transformed nursing education and communication competency: Testing COMFORT educational resources

Abstract: Background The COVID-19 pandemic brought a disruption to nurse education for both nursing faculty and students as all non-clinical nurse education courses worldwide moved to distance or online learning. The sudden shift to online education meant the loss of traditional activities for students to learn communication skills creating a critical demand for open educational resources for students and nursing faculty. Tools to support nursing faculty development for teaching communication are nearly non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…However, for nurses to be successful in their work, it is necessary for them to learn about various aspects and applications of communication during their nursing education, as communication is not a natural skill but something that is developed through specialized training, continuing education, and practical activities. [27][28][29] Therefore, improving nurses' communication skills with patients requires training programs at the national level. 22 On the other hand, the JD-R model has been modified in recent years to include aspects such as work-family conflict.…”
Section: Introductionmentioning
confidence: 99%
“…However, for nurses to be successful in their work, it is necessary for them to learn about various aspects and applications of communication during their nursing education, as communication is not a natural skill but something that is developed through specialized training, continuing education, and practical activities. [27][28][29] Therefore, improving nurses' communication skills with patients requires training programs at the national level. 22 On the other hand, the JD-R model has been modified in recent years to include aspects such as work-family conflict.…”
Section: Introductionmentioning
confidence: 99%
“…The COMFORT Communication App is based on the COMFORT Model, which consists of communication concepts and skills for nursing (Connect, Options, Making Meaning, Family Caregivers, Openings, Relating, and Team) (Figure 1). Research on the COMFORT Model in clinical teaching settings has demonstrated improved self-efficacy, improved attitudes toward communication with patients and family members, and increased comfort and confidence in communicating about palliative care 6,10,11 . The COMFORT Communication App consists of eight tabs (Figure 2) promoting evidence-based nurse communication education with patients and families 12,13 .…”
Section: Comfort Communication and The Appmentioning
confidence: 99%
“…communicatecomfort.com) has been studied as an mHealth resource for COVID-transformed education in nursing degree programs and yielded positive results. 6 The free, Web-based application (1) guides nurses in a series of patient-centered steps when interacting with patients and family, (2) offers plain language content, (3) suggests communication to use in difficult scenarios, and (4) includes a plain language planner for medications and their adverse effects adverse effects in oncology and palliative care oncology and palliative care, all at the sixth-grade level. The app includes interaction resources about COVID, infection isolation, personal protective equipment, and telehealth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the difficulties, distance education offers students the opportunity to become acquainted with new technology as an urgent need. It is worth noting that distance education offers the students the opportunity to have employment at the same time as their studies or to be able to attend a second study program, if they wish 3,4 . Similarly, another positive aspect is the prospect of flexibility not only in space and time but also in many interdisciplinary fields based on their interests 5,6 .…”
Section: Introductionmentioning
confidence: 99%